2001
DOI: 10.1046/j.1432-1327.2001.01992.x
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of the Golgi‐localized enzyme α‐mannosidase IIx in Chinese hamster ovary cells results in the conversion of hexamannosyl‐N‐acetylchitobiose to tetramannosyl‐N‐acetylchitobiose in the N‐glycan‐processing pathway

Abstract: Keywords: a-mannosidase II; a-mannosidase IIx; Golgi; HPLC; N-glycan.The major biosynthetic pathway of N-glycans in higher organisms has been established [1]. In the endoplasmic reticulum (ER), a lipid-linked glucosylated high-mannose oligosaccharide is transferred from the dolichol donor to a protein acceptor. High-mannose oligosaccharides are then processed by a-glucosidases and a-1,2 mannosidases (MI) to produce Man 5 GlcNAc 2 (M 5 Gn 2 ). A key conversion of this oligosaccharide to complex-type oligosaccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…5A), indicating that full-length MX can rescue the complex N-glycan deficiency in double-null cells. In vitro enzyme assays using the soluble catalytic domain of MX also detected activity toward a GlcNAc 1 Man 5 GlcNAc 2 substrate in contrast to prior studies using a recombinant form of human MX (17). We recently identified alternatively spliced forms and sequence polymorphisms of human MX and confirmed that several of these transcripts encode enzymes active toward GlcNAc 1 Man 5 GlcNAc 2 , whereas a splice variant used in our previous study (17) was not active toward high-mannose oligosaccharides or GlcNAc 1 Man 5 GlcNAc 2 (H. Singh, T.O.A., M.N.F., and K.W.M., unpublished data).…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…5A), indicating that full-length MX can rescue the complex N-glycan deficiency in double-null cells. In vitro enzyme assays using the soluble catalytic domain of MX also detected activity toward a GlcNAc 1 Man 5 GlcNAc 2 substrate in contrast to prior studies using a recombinant form of human MX (17). We recently identified alternatively spliced forms and sequence polymorphisms of human MX and confirmed that several of these transcripts encode enzymes active toward GlcNAc 1 Man 5 GlcNAc 2 , whereas a splice variant used in our previous study (17) was not active toward high-mannose oligosaccharides or GlcNAc 1 Man 5 GlcNAc 2 (H. Singh, T.O.A., M.N.F., and K.W.M., unpublished data).…”
Section: Discussioncontrasting
confidence: 61%
“…Previous studies suggest that human MX is catalytically active and plays a role in N-glycan biosynthesis (16)(17)(18). When mouse Man2a2, the orthologue of human MAN2A2, was disrupted, MX-nulls were apparently normal, except that mutant males were subfertile (18).…”
mentioning
confidence: 99%
“…The synthesis of N-glycans initiates from the so-called high-mannose-type oligosaccharide, which is then trimmed by the processing glucosidases and mannosidases. This figure illustrates the reactions surrounding MII, including MX (Akama et al, 2002;Oh-eda et al, 2001) and the putative enzyme MIII (Chui et al, 1997). or complex-type N-glycan, this result demonstrates that highmannose-type N-glycans alone can not support embryonic development beyond E9.5-10.5 in the mouse.…”
Section: Gene Knockout Mouse Approach Revealed the In Vivo Role Of N-mentioning
confidence: 98%
“…Overexpression experiments with MX suggest that MX hydrolyzes Man 6 GlcNAc 2 to Man 4 GlcNAc 2 in the Golgi ( Fig. 1) (Oh-eda et al, 2001). However, the substrate specificity of MX has not been defined unambiguously by in vitro experiments due to its weak enzymatic activity (Oh-eda et al, 2001).…”
Section: Identification Of MX In Human Genomementioning
confidence: 99%
See 1 more Smart Citation